2014
DOI: 10.1182/blood-2014-03-560227
|View full text |Cite
|
Sign up to set email alerts
|

Driver somatic mutations identify distinct disease entities within myeloid neoplasms with myelodysplasia

Abstract: Key Points• Different driver mutations have distinct effects on phenotype of myelodysplastic syndromes (MDS) and myelodysplastic/ myeloproliferative neoplasms (MDS/MPN).• Accounting for driver mutations may allow a classification of these disorders that is considerably relevant for clinical decision-making. Irrespective of driver somatic mutations, a threshold of 5% bone marrow blasts retained a significant discriminant value for identifying cases with clonal evolution. Comutation of TET2 and SRSF2 was highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
162
0
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 226 publications
(178 citation statements)
references
References 35 publications
(34 reference statements)
5
162
0
11
Order By: Relevance
“…Mutations in TET2, SRSF2 and ASXL1 are by far the most frequent, being present in ~30-50% of cases each, and even though none of these oncogenes is specific of CMML amongst other myeloid neoplasms, the combination of TET2/SRSF2 mutations is highly suggestive of CMML [39]. As discussed below, mutations in signaling transduction genes are more frequent in patients with MP-CMML.…”
Section: Molecular Lesions and Pathogenesismentioning
confidence: 99%
“…Mutations in TET2, SRSF2 and ASXL1 are by far the most frequent, being present in ~30-50% of cases each, and even though none of these oncogenes is specific of CMML amongst other myeloid neoplasms, the combination of TET2/SRSF2 mutations is highly suggestive of CMML [39]. As discussed below, mutations in signaling transduction genes are more frequent in patients with MP-CMML.…”
Section: Molecular Lesions and Pathogenesismentioning
confidence: 99%
“…The prognostic relevance of gene mutations may differ among MDS/MPN. For instance, SF3B1 mutations have been found to be important prognostically in the RARS-T subgroup, 29,47 whereas their impact on the outcome of CMML patients remains to be investigated. How these aberrations may later be incorporated into risk models for these diseases remains unclear, and clarifying this information to properly incorporate these aberrations in prognostication is a priority.…”
Section: Risk Stratification Modelsmentioning
confidence: 99%
“…High frequencies have been detected only in small cohorts: 12.5% (n=24) 7 and 25.0% (n=12), 10 whereas a large multicenter study reported a frequency of only 1.1% (n=95).…”
mentioning
confidence: 99%